Gender Equality and Equity with Mubadalah Concept and Its Implementation in Islamic Education - Werdiningsih, Wilis; Natsir, Ahmad (ADDIN, 2020)
Gender equality study is the study that will continously be discussed in human life. The study of gender examines the diverse roles of women and men in community life. The concept of mubadalah is of the new studies in gender equality. The concept of mubadalah is way of looking at two relations, namely man and woman, in which both of them as dignified human beings who are able to take advantages of all aspects of life for their good. Education is an important means of educating people who are knowledgeable and have noble character. Gender-based education is the foundation in creating a gender responsive young generation. This study aims to examine more deeply the concept of mubadalah and its implementation in Islamic education. This study used qualitative approach and the type of this research is library research. Data were obtained from various sources relate to the concept of mubadalah and Islamic education. The results show that the concept of mubadalah is one of the concepts of gender equality which can be used as a reference for understanding gender equality and equity that seeks to see women and men as servants of Allah swt. which is the subject of the texts in Al-Qur’an as well as in their interpretation. Education in an Islamic perspective becomes a forum for teaching gender equality through the design of a gender responsive education component.